In Vitro Evaluation Of The Ferrule Effect And Post Material On Failure Load And Mode In Endodontically Treated Teeth - Abbas, Mahmood Alayham (2012)

(untitled)
There are still controversy regarding the ferrule effect and a better bonded prefabricated posts on strength of endodontically treated teeth. The aim of this study was to compare the effect of ferrule and two types of bonded post material on failure load and failure mode of restored endodontically treated teeth.